2021
DOI: 10.1093/europace/euaa327
|View full text |Cite
|
Sign up to set email alerts
|

High-power short duration vs. conventional radiofrequency ablation of atrial fibrillation: a systematic review and meta-analysis

Abstract: Aims We sought to compare the effectiveness and safety of high-power short-duration (HPSD) radiofrequency ablation (RFA) with conventional RFA in patients with atrial fibrillation (AF). Methods and results MEDLINE, Cochrane, and ClinicalTrials.gov databases were searched until 15 May 2020 for relevant studies comparing HPSD vs. conventional RFA in patients undergoing initial catheter ablation for AF. A total of 15 studies inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 27 publications
9
79
0
Order By: Relevance
“…For the short‐term efficacy outcomes, our study revealed that HPSD RFCA had better first‐pass PVI than LPLD RFCA. This result was consistent with the findings from the previous meta‐analysis 46‐48 . Moreover, the HPSD approach was also associated with a lower risk of PV reconnection.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…For the short‐term efficacy outcomes, our study revealed that HPSD RFCA had better first‐pass PVI than LPLD RFCA. This result was consistent with the findings from the previous meta‐analysis 46‐48 . Moreover, the HPSD approach was also associated with a lower risk of PV reconnection.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the HPSD approach was also associated with a lower risk of PV reconnection. The data about the risk of PV reconnection were provided by the meta‐analysis study from Ravi et al 48 and our results supported that. For the long‐term efficacy outcomes, our study demonstrated that performing HPSD RFCA effectively reduced the risk of recurrent AF.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Several prospective randomized and non-randomized studies comparing LP-LD versus HP-SD show that HP-SD is associated with higher first-pass PV isolation and significantly shorter procedural, ablation and fluoroscopy times compared with LP-LD [5] , [6] , [7] , [8] , [9] , [10] . Meta-analysis data demonstrate that HP-SD was associated with better procedural effectiveness when compared with conventional LP-LD ablation with comparable low rate of complications and esophageal thermal injury and shorter procedural duration [11] , [12] .…”
Section: Correspondencementioning
confidence: 99%